Dioscorea Extract (DA-9801) Modulates Markers of Peripheral Neuropathy in Type 2 Diabetic db/db Mice - Moon, Eunjung; Lee, Sung Ok; Kang, Tong Ho; Kim, Hye Ju; Choi, Sang Zin; Son, Mi-Won; Kim, Sun Yeou (Biomolecules & therapeutics, 2014)
The purpose of this study was to investigate the therapeutic effects of DA-9801, an optimized extract of Dioscorea species, on diabetic peripheral neuropathy in a type 2 diabetic animal model. In this study, db/db mice were treated with DA-9801 (30 and 100 mg/kg, daily, p.o.) for 12 weeks. DA-9801 reduced the blood glucose levels and increased the withdrawal latencies in hot plate tests. Moreover, it prevented nerve damage based on increased nerve conduction velocity and ultrastructural changes. Decrease of nerve growth factor (NGF) may have a detrimental effect on diabetic neuropathy. We previously reported NGF regulatory properties of the Dioscorea genus. In this study, DA-9801 induced NGF production in rat primary astrocytes. In addition, it increased NGF levels in the sciatic nerve and the plasma of type 2 diabetic animals. DA-9801 also increased neurite outgrowth and mRNA expression of Tieg1/Klf10, an NGF target gene, in PC12 cells. These results demonstrated the attenuation of diabetic peripheral neuropathy by oral treatment with DA-9801 via NGF regulation. DA-9801 is currently being evaluated in a phase II clinical study.